Development of Short Story Basic Movement Trhow-Cacth at Elementary School - Lanos, Muhsana El Cintami; Lestari, Hikmah; Iswana, Bayu; Okilanda, Ardo (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
This study aims to develop a learning medium for short storybooks of basic motion material for catching. The research method used is to adopt the research and development (R & D) model of Borg and Gall up to the 3rd stage, namely 1) Research and Information Collection, 2) Planning, 3) Develop Preliminary of Product Data collection using observation, questionnaires, and interviews, Data analysis techniques using qualitative and quantitative data. The stages start from (1) Research and information collecting, the results of the needs analysis show that there is a need for updates to make learning media in the form of short storybooks that are more innovative and interesting so that students learn data anywhere at any time without being limited by space and time. (2) Planning, making a research plan by forming a team according to the expertise needed to help develop research products. (3) Develop Preliminary of Product to create a model / design of learning book products that are outlined in interesting images and short stories to improve student reading literacy and theoretical feasibility tests by involving expert judgments,  namely learning experts, material experts and media experts.   Hasil research shows that Learning Media in the form of short storybooks of basic motion material for throwing is declared suitable for use in elementary school students.